Effect of Synbiotics Administering Probiotics_FM and MOS In the Ration on Broiler Carcass Weight - Sihite, Herlin Rusadi; Mairizal, Mairizal; Akmal, Akmal (Universitas Bengkulu, 2024)
The use of AGP in broiler farming is for disease treatment and anti-stress, and AGP is also used to stimulate broiler growth. However, continuous use of AGP has been prohibited because it causes resistance to pathogenic bacteria and causes residue for consumers. Therefore, it is important to find a safe replacement for AGP, which can be done using synbiotics. This study aims to determine the effect of providing synbiotics from probiotic Probio_FM and prebiotic Mannan Oligosaccharide (MOS) in the diet on broiler carcass weight. The design used in this research was a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatment in this study consisted of P0: Commercial ration + 0% Synbiotic from Probio_FM and MOS, P1: Commercial ration + 0.25 % Synbiotic from Probio_FM and MOS, P2: Cormersil ration + 0.50% Synbiotic from Probio_FM and MOS, P3: Cormersil ration + 0.75% Synbiotic from Probio_FM and MOS, P4: Commercial ration+1% Synbiotic from Probio_FM and MOS. The variables observed in this research were feed consumption, slaughter weight, absolute carcass weight and relative carcass weight. Data were analyzed using variance analysis (ANOVA) with Duncan's advanced test. The results showed that the addition of synbiotics from Probio_FM and MOS had a significant effect (P˂0.05) on feed consumption, slaughter weight and absolute carcass weight but had no significant impact (P˃0.05) on relative carcass weight. It was concluded that administering synbiotics from Probio_FM and MOS at 0.25%, 0.50%, 0.75%, and 1% in the ration could increase broiler chicken carcass weight. The research conclusion of the study was that giving synbiotics from Probio_FM and MOS was more effective at a level of 0.25% -0,5%, which was able to increase broiler carcass weight.